The 1st students choice TOEFL ( test of english as a foreign language ) test strategy for structure and written expression : strategi menjawab soal structure and written expression dalam tes TOEFL - Riyanto, Slamet (Pustaka Pelajar, 2008)
xi, 333 hlm.; 23 cm